Victimization and depressive symptomology in transgender adults: The mediating role of avoidant coping. - White Hughto, Jaclyn M; Pachankis, John E; Willie, Tiara C; Reisner, Sari L (Journal of counseling psychology, 2017)
Victimization and depressive distress symptoms represent serious and interconnected public health problems facing transgender communities. Avoidant coping is hypothesized to temporarily alleviate the stress of victimization, but has potential long-term mental and behavioral health costs, such as increasing the probability of depressive symptoms. A community sample of 412 transgender adults (M age = 32.7, SD = 12.8) completed a one-time survey capturing multiple forms of victimization (i.e., everyday discrimination, bullying, physical assault by family, verbal harassment by family, childhood sexual abuse, intimate partner violence), avoidant coping, and past-week depressive symptomology. Structural equation modeling examined the mediating role of avoidant coping in the association between victimization and depressive symptomology. A latent victimization variable comprised of 6 measures of victimization was positively associated with avoidant coping, which in turn was positively associated with depressive symptoms. Victimization was also positively associated with depressive symptomology both directly and indirectly through avoidant coping. Avoidant coping represents a potentially useful intervention target for clinicians aiming to reduce the mental health sequelae of victimization in this highly stigmatized and vulnerable population. (PsycINFO Database Record
Keywords: Adaptation, Psychological; Adolescent; Adult; Aged; Crime Victims; Depression; Female; Humans; Male; Massachusetts; Middle Aged; Social Stigma; Spouse Abuse; Surveys and Questionnaires; Transgender Persons